Photosynthetic response to different light intensities, water status and leaf age of two Berberis species (Berberidaceae) of Patagonia steppe, Argentina. - Peri, Pablo Luis; Arena, Miriam Elizabeth; Martínez Pastur, Guillermo José; Lencinas, María Vanessa (Elsevier, 2022)
Net photosynthetic rate (A) and stomatal conductance (gs) from leaves of Berberis buxifolia and Berberis heterophylla saplings were measured under different conditions of radiation and water availability and for leaves of different ages. Comparative studies of basic physiological performance would give insight how these shrubs survive and grow under this austral extreme ecosystem. B. buxifolia had higher A values than B. heterophylla for all light intensities measured. Values of gs for both Berberis species also declined as light intensity decreased. There was a negative relationship between A and water stress expressed as pre-dawn leaf water potential (jlp) where the reduction in gs was the main factor that reduced A in both species. Also, A and gs of Berberis plants increased rapidly during the first days after leaf unfolding, reached a maximum value when the leaf was completely expanded, and then declined. These results could be used to estimate the responses of saplings to environmental conditions under the dynamic of natural stands in this austral extreme ecosystem and for restoration plans.